Teaching ESp or EGP in Bohicon Technical School? Bridging the Teacher Training Gap - YESSOUFOU, AKIMI; SEGOH, Gilberte L. (My University, 2019)
In Benin, although trainee teachers are trained to teach English as a foreign language for general purposes, some graduates are posted into vocational schools where the teaching of ESP is required of them. This paper aims at probing into the coping strategies of these EFL teachers. Without proper training in teaching English for specific purposes, without an appropriate curriculum, without adequate resources, do they teach English for general purposes or English for specific purposes? To answer this question, the paper relies on documentary investigation, interviews with EFL teachers and focus group discussion with students at LyteB. Qualitative data analysis discloses that despite their effort to bridge the teacher training gap, EFL teachers in vocational schools spend more time in teaching English for general purposes, because of structural obstacles, and the status of English as a 'second class' subject in vocational schools. This discrepancy flaws the training of graduates who acquire technical competences that they are unable to value in an English work setting.
Keywords: Teacher qualification; English for specific purposes; Vocational education